MoS2-Si3N4-based SPR biosensor for the detection of malaria at different stages: A theoretical insight - Talia Tene; Marco Guevara; Isaías Caicedo; Jose Luis Granizo Jara; Myrian Borja; Lala Gahramanli; Cristian Vacacela Gomez; Stefano Bellucci (Biosensors and Bioelectronics: X, 2025)
The accurate differentiation of malaria stages is essential for effective treatment and epidemiological control. This work presents a theoretical analysis of a multilayer surface plasmon resonance (SPR) biosensor for malaria stage detection based on refractive index variations of infected red blood cells. The sensor combines silver, silicon nitride (Si3N4), monolayer molybdenum disulfide (MoS2), and thiol-functionalized single-stranded DNA (ssDNA) on a BK7 prism. Using the transfer matrix method (TMM), we evaluate the sensor performance across Ring, Trophozoite, and Schizont stages through sensitivity, full width at half maximum (FWHM), quality factor (QF), detection accuracy (DA), limit of detection (LoD), and comprehensive sensitivity factor (CSF). The optimized configuration achieves angular sensitivities of 318.2 (Ring), 268.9 (Trophozoite), and 244.8 (Schizont) °/RIU, demonstrating clear stage discrimination and competitive performance compared to reported multilayer SPR sensors. The layered architecture was designed with experimentally accessible materials and configurations, supporting future translation to stage-specific diagnostic platforms.